Democracia e inconstitucionalidade de coligações assimétricas: o caso da Emenda Constitucional n.º 52/2006 - Silva, André Santos (2016)
This thesis aims, firstly, to identify in which way the elections rules, especially those linked to party coalitions, are related with the essential and constitutionally established rules that founded the Democracy, starting from a required theoretical study in order to conclude for the unconstitutionality of any provisions contrary to Constitutional Democracy outlined by the 1988 Constitution. It is well-known that the concept of a Democratic State varies according to the greater and effective participation of the people not only in elections but also in a number of decisions by the political power, through a mechanism of "rules of the game" previously established in the Constitution prevailing the will of the majority represented over the losing minority. Although others constitutional mechanisms of popular participation in political decisions deserve proper scholarly attention, this work seeks to analyze, precisely, the context and the rules of elections, in order to verify the constitutionality of organizational procedures of those who intend, through political parties, to exercise, representatively, the power of the people in decision-making. Nevertheless, taking into account that all power emanates from the people, the analysis of the rules governing the political and legislative process has the role to gather legal arguments which allows to state whether the rules of the game modified by the political power established by Constitutional Amendment n.º 52/2006 - which expressly allowed the formation of asymmetric party coalitions at the federal and state level - are compatible or not with the Constitution and with the idea of Constitutional Democracy based on the theory of unconstitutionality of constitutional amendments